1996
DOI: 10.1021/ma946430p
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Diffusion of Concentrated Polymer Solutions:  A Static and Dynamic Light Scattering Study of Polystyrene in DOP

Abstract: Solutions of polystyrene in DOP were studied as a function of the concentration (0.2−0.9 g/mL) and temperature (−10 to +130 °C) using static and dynamic light scattering. The concentration and temperature dependence of the cooperative diffusion coefficient and the osmotic modulus were determined. The concentration and temperature dependences of the cooperative diffusion coefficient are explained in terms of the concentration and temperature dependence of the osmotic modulus and the solvent mobility. At the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…15,[59][60][61][62] There has been an ongoing discussion in the literature about the correct formulation of the collective diffusion coefficient of polymer solutions within the frictional formalism. Here, we follow the notation used by Nicolai and Brown,4 which is in agreement with arguments of Vink. 63 Other authors omit the factor (1Ϫ) 2 in Eq.…”
Section: A Mass Diffusion Coefficientmentioning
confidence: 98%
See 1 more Smart Citation
“…15,[59][60][61][62] There has been an ongoing discussion in the literature about the correct formulation of the collective diffusion coefficient of polymer solutions within the frictional formalism. Here, we follow the notation used by Nicolai and Brown,4 which is in agreement with arguments of Vink. 63 Other authors omit the factor (1Ϫ) 2 in Eq.…”
Section: A Mass Diffusion Coefficientmentioning
confidence: 98%
“…Based on a model of Vrentas et al, 66 it is shown in Ref. 4 that D can be written in a Stokes-Einstein-type form,…”
Section: A Mass Diffusion Coefficientmentioning
confidence: 99%
“…40,114,115 Experiments around the Y condition indicate that the solvent quality has a profound effect on the slow relaxation. [48][49][50][51][52][53][54] Actually, not everyone accepts or recognizes such a slow mode, even though it has been repeatedly observed for more than three decades. In the last two decades, advancements of LLS instrumentation, including the full digital time correlator and computer, have made the dynamic study of semidilute solutions much easier and more reliable, but the preparation of dust-free viscous semidilute solutions still remains an experimental challenge.…”
Section: Llsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] These include: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] These include:…”
Section: Plasticizer Diffusion Rate and The Methods Of Studymentioning
confidence: 99%